Regulation of insulin secretion: a matter of phase control and amplitude modulation - Henquin, J. C (Diabetologia, 2009)
The consensus model of stimulus-secretion coupling in beta cells attributes glucose-induced insulin secretion to a sequence of events involving acceleration of metabolism, closure of ATP-sensitive K⁺ channels, depolarisation, influx of Ca²⁺ and a rise in cytosolic free Ca²⁺ concentration ([Ca²⁺]c). This triggering pathway is essential, but would not be very efficient if glucose did not also activate a metabolic amplifying pathway that does not raise [Ca²⁺]c further but augments the action of triggering Ca²⁺ on exocytosis. This review discusses how both pathways interact to achieve temporal control and amplitude modulation of biphasic insulin secretion. First-phase insulin secretion is triggered by the rise in [Ca²⁺]c that occurs synchronously in all beta cells of every islet in response to a sudden increase in the glucose concentration. Its time course and duration are shaped by those of the Ca²⁺ signal, and its amplitude is modulated by the magnitude of the [Ca²⁺]c rise and, substantially, by amplifying mechanisms. During the second phase, synchronous [Ca²⁺]c oscillations in all beta cells of an individual islet induce pulsatile insulin secretion, but these features of the signal and response are dampened in groups of intrinsically asynchronous islets. Glucose has hardly any influence on the amplitude of [Ca²⁺]c oscillations and mainly controls the time course of triggering signal. Amplitude modulation of insulin secretion pulses largely depends on the amplifying pathway. There are more similarities than differences between the two phases of glucose-induced insulin secretion. Both are subject to the same dual, hierarchical control over time and amplitude by triggering and amplifying pathways, suggesting that the second phase is a sequence of iterations of the first phase.